Effects of EGF, FGF, and PDGF on Canine Chondrocytes in Three-Dimensional Culture - Cook, J. L.; Kreeger, J. M.; Payne, J. T.; Tomlinson, J. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
Three-dimensional (3-D) culture of chondrocytes has been shown to promote cell proliferation, differentiation, and production of matrix while providing for cell morphology and matrix characteristics that resemble normal articular cartilage (1-3). In a recently published study, enhanced glycosaminoglycan (GAG) production was demonstrated in canine chondrocytes in 3-D culture on cancellous bone substrate (3). The effects of growth factors known to be present in cryopreserved bone were suggested to be responsible. Various growth factors including epidermal growth factor (EGF), fibroblast growth factor (FGF), and plateletderived growth factor (PDGF) have been shown to enhance chondrocyte DNA production, mitotic activity, and matrix production (5-10). The objective of the study reported here was to evaluate the effects of one concentration of EGF, FGF, and PDGF on canine chondrocyte proliferation and production of normal matrix constituents in 3-D culture.Canine articular chondrocytes were cultured in three-dimensional medium for 25 days. EGF, FGF, and PDGF were added to the culture medium. Chondrocytes in 3-D culture maintained viability and differentiation. Cell morphology and matrix production resembled that of intact hyaline cartilage. Significant differences with respect to cell counts, glycosaminoglycan concentration, or collagen type II immuno-reactivity as the result of added growth factors were not found.
Keywords: Chondrocytes; three-dimensional culture; growth factors; glycosaminoglycans; dimethylmethylene blue; collagen type II